A review of factors associated with the utilization of healthcare services and strategies for improving postpartum care in Africa - Belemsaga, Danielle Yugbare; Kouanda, Seni; Goujon, Anne; Kiendrebeogo, Joel A.; Duysburgh, Els; Degomme, Olivier; Temmerman, Marleen (Afrika Focus, 2015)
Reducing maternal mortality continues to be a major challenge for African countries. We conducted a literature review to identify the factors associated with the utilization of maternal and child healthcare services during the postpartum period and the strategies for strengthening postpartum healthcare in Africa. We carried out an electronic search in several databases of texts published between 1995 and 2012 related to maternal and child health. Seventyfive publications fitted the eligibility criteria. Our analysis shows that to a large extent the socio-economic context was dominant among the factors associated with the quality and utilization of postpartum services. The best interventions were those on immediate postpartum maternal care combining several intervention packages such as community mobilization and provision of services, community outreach services and health training. The integration within health facilities of mother and child clinics was shown to contribute signifiHealthcantly to improving the frequency of mothers’ postpartum visits. Key words: postpartum care, postnatal care, maternal and child health, health interventions, health strategies, sub-Saharan Africa